1991
DOI: 10.1002/mrm.1910170125
|View full text |Cite
|
Sign up to set email alerts
|

Surface coil spectroscopic imaging: Time and spatial evolution of lactate production following fluid percussion brain injury

Abstract: Detailed temporal and spatial distributions of lactate production are presented for graded fluid-percussion brain injury in the rat. A one-dimensional proton spin-echo spectroscopic imaging (1D SESI) technique, performed with a surface coil, is presented and evaluated. This technique, which represents a practical compromise, provides spatially localized proton nuclear magnetic resonance (NMR) brain spectra from a series of small voxels (less than 0.15 cm3) in less than 10 min, thus enabling both spatial and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Moreover, animals demonstrating significantly different neurological outcomes showed no significant differences in brain lactic acid concentration, suggesting that brain lactate accumulation per se is not related to injury outcome. Subsequent studies have shown that the lactic acid may diffuse from the injured tissue into the noninjured hemisphere (Cohen et al, 1991) and into the cerebrospinal fluid (Inao et al, 1988;Yoshida and Marmarou, 1991), The latter study also demonstrated that lactic acid in cerebrospinal fluid may also derive from systemic sources.…”
Section: Intracellular Ph and Lactic Acidmentioning
confidence: 87%
“…Moreover, animals demonstrating significantly different neurological outcomes showed no significant differences in brain lactic acid concentration, suggesting that brain lactate accumulation per se is not related to injury outcome. Subsequent studies have shown that the lactic acid may diffuse from the injured tissue into the noninjured hemisphere (Cohen et al, 1991) and into the cerebrospinal fluid (Inao et al, 1988;Yoshida and Marmarou, 1991), The latter study also demonstrated that lactic acid in cerebrospinal fluid may also derive from systemic sources.…”
Section: Intracellular Ph and Lactic Acidmentioning
confidence: 87%
“…Increases in cerebral lactate after TBI typically begin early (minutes to hours) after injury in adult animal models of both fluid percussion (Cohen et al, 1991;Inao et al, 1988;McIntosh et al, 1987) and CCI (Brooks et al, 2001;Schuhmann et al, 2003). Increased lactate can result from several potential mechanisms, such as post-injury increases in glycolysis (Kawamata et al, 1995;Yoshino et al, 1991) and reduced oxidative metabolism, with oxidative injury to key metabolic enzymes (Bogaert et al, 2000;Kochanek et al, 2006;Martin et al, 2005;Opii et al, 2007;Richards et al, 2006;Robertson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies were conducted to verify that the inverted lH signal at 1.32 ppm was from lactate in brain. First, one-dimensional spectroscopic imaging experi-ments were performed with the same surface coil using a pulse sequence recently described by our group (Cohen et al, 1989). The spectroscopic imaging sequence permitted concomitant acquisition of signals from a series of slices, 1 mm thick, through the head.…”
Section: Methodsmentioning
confidence: 99%